Analysis on production factors and marketing of corn - Muh Syarif; Samsuki Samsuki; Achmad Amzeri; Zainul Azmi (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2022)
Madura has a corn farming area of approximately 300,000 hectares wide. However, its productivity is still low, about 2.15 tons per hectare. The purpose of this study was to determine the effect of production factors and the efficiency of corn marketing channels in Pamekasan Regency. Research respondents are farmers, retailers, collectors, and wholesalers in Batu Kerbuy village and Pademawu village, Pamekasan Regency. The total respondents were 60 farmers who were determined using the random sampling method and 12 traders who were determined using the tracing sampling method. The analysis techniques used were the Cobb-Douglas function variables, farmer's share, marketing margin, and marketing efficiency. The results showed that five production variables simultaneously affected corn production. Partially, there were three variables with a highly significant effect, i.e. labor, pesticides, and fertilizers, while there were another two variables, i.e. land area and seeds, with no significant effect. There were five corn marketing channels in Pamekasan Regency, with marketing channel I being more efficient than the others.